Evaluation of Mechanical Properties and Filler Interaction in the Field of SLA Polymeric Additive Manufacturing - Jirků, Petr; Urban, Jiří; Müller, Miroslav; Kolář, Viktor; Chandan, Vijay; Svobodová, Jaroslava; Mishra, Rajesh Kumar; Jamshaid, Hafsa (Materials (Basel, Switzerland), 2023)
The paper deals with research focused on the use of fillers in the field of polymeric materials produced by additive technology SLA (stereolithography). The aim of the research is to evaluate 3D printing parameters, the mechanical properties (tensile strength, hardness), and the interaction of individual phases (polymer matrix and filler) in composite materials using SEM analysis. The tested fillers were cotton flakes and ground carbon fibres in different proportions. For the photosensitive resins, the use of cotton flakes as filler was found to have a positive effect on the mechanical properties not only under static but also under cyclic loading, which is a common cause of material failure in practice. The cyclic stress reference value was set at an amplitude of 5-50% of the maximum force required to break the pure resin in a static tensile test. A positive effect of fillers on the cyclic stress life of materials was demonstrated. The service life of pure resin was only 168 ± 29 cycles. The service life of materials with fillers increased to approximately 400 to 540 cycles for carbon fibre-based fillers and nearly 1000 cycles for cotton flake-based fillers, respectively. In this paper, new composite materials suitable for the use of SLA additive manufacturing techniques are presented. Research demonstrated the possibilities of adding cotton-based fillers in low-cost, commercially available resins. Furthermore, the importance of material research under cyclic loading was demonstrated.
Keywords: polymer composite; cyclic loading; 3D printing; low cycle test; carbon filler; cotton filler